Unbalance and Harmonic disturbance attenuation of a flexible shaft with active magnetic bearings. (15th August 2019) - Noshadi, Amin; Zolfagharian, Ali
Highlights: Disturbance attenuation of flexible shaft in variable rotational speeds. Development of a repetitive disturbance observer-based controller. Experimental performance evaluation of the developed algorithm on a multi-input-multi-output active magnetic bearing system. Abstract: Active magnetic bearings (AMB)s are attractive replacement of hydrostatic bearings mainly due to the absence of mechanical frictions, high-precision and low maintenance costs in high-speed and high-precision applications. However, they are inherently open-loop unstable and hence feedback controllers are essential for stabilisation of AMB equipped systems. This paper studies the robust stabilization and harmonic disturbance rejection of a flexible shaft and an AMB system. Firstly, a H ∞ loop-shaping method is utilized to stabilize the flexible shaft while the system is stationary. Then, an inner-loop is introduced to the feedback loop to minimize vibration performance measures while the shaft is in rotation at various rotational speeds. The inner-loop aims to combine the features of the common disturbance observer-based controllers and the repetitive controllers. The performance of the developed algorithm is experimentally verified on a multi-input-multi-output active magnetic bearing system. The experimental results demonstrate that the combination of the feedback H ∞ - controller and the inner-loop repetitive disturbance observer-based controller (RDOBC) not only robustly stabilizes the AMB system and greatly reduces the gain amplification of harmonic disturbances at fundamental frequencies, but it also reduces the gain amplification of the non-repetitive frequencies substantially.